ERDKUNDE - 50 Jahrgänge ,Archiv für wissenschaftliche Geographie’.: Ein Rückblick und Ausblick - Böhm, Hans; Ehlers, Eckart (ERDKUNDE, 1996)
In 1980 CH. D. HARRIS characterized Erdkunde as a leading international scientific periodical among the four most important of the German-language geographical journals. It owes this assessment not least to the efforts of CARL TROLL, who found ways and means in the years immediately after World War 11 to set up an organ for publications that served to re-establish German geography’ s contacts, which had largely been disrupted by the war. Due to regulations issued by the Allied Powers the re-organisation of geographical publishing amounted to a formal break with the traditions of the subject: in respect of subject matter and content, however, the new foundation was to document the logically consistent continuation of a pure scientific research tradition - as opposed to one under the influence of National Socialist ideology - while deliberately ignoring all experience with reference to subject-specific applications. In his 1947 preface TROLL outlined four goals he intended to attain with his publication. Original papers and up-to date reports on research were to present new insights across the entire field of geography, and review articles were to supply critical references on the state of research in specialized fields of the subject. Beyond this, he charged Erdkunde with the obligation to cultivate links with related subjects. Finally, there were to be detailed reviews of recent geographical publications and of foreign publications which had appeared during the war years. The material brought together in Table 1 shows that throughout these decades Erdkunde has maintained an approximately even balance of papers in the fields of physical geography and human geography, yet even at this rough level of differentiation there is evidence of shifting accents which characterize developments in German geography over the past 50 years: physical geography has moved from concern for problems in geomorphology to addressing those of climatic geography and high mountain landscape ecology, while human geography has registered a decline of general cultural contributions in favour of more specialized problems concerning population, settlement and economic geography. In Erdkunde ’s early years especially, discussions of landscape, regional science and landscape ecology came to the fore. As E. FISCHER had already noted in 1948, they form a specific characteristic of German geography. The occasion of a critical retrospective over the 50 years of Erdkunde raises the question of possible future perspectives for the periodical. In keeping with the spirit of its founder, Erdkunde, at a time of increasing globalisation even in geographical research, might develop from being a mouthpiece for German geography to becoming an organ of the international scientific community.